Interfacing Manual and Machine Composition. - Anders, Torsten; Miranda, EduardoReck (Contemporary Music Review, 2009)
Computer-aided composition (CAC) is situated somewhere in the middle between manual composition and automated composition that is performed autonomously by a computer program. Computers cannot make aesthetic decisions in their own right. They can only follow orders. Aesthetic decisions are made by composers, both via the design of computer programs and by manually controlling these programs. The latter plays an important part in CAC. The composition process typically involves much emending and revising: changing how a computer program is controlled is easier and allows for a more intuitive way of working than changing the program itself. This paper argues that constraint programming is a particularly suitable programming paradigm for flexibly interfacing manual and machine composition.